SOCIAL CRITICAL ANALYSIS OF THE SHORT STORY DINDING TIME BY DANARTO USING THE MIMETIC APPROACH AS AN ALTERNATIVE LEARNING MATERIAL FOR STUDENTS IN PHASE F - Risna Dara; Titin Nurhayatin; Rani Siti Fitriani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research aims to analyze the social criticism conveyed through the short story Wall of Time by Danarto, with a focus on issues of poverty, crime, family disorganization, problems of the younger generation, war, violations of norms, population problems, and environmental problems. This short story describes the social tensions and pressures of individual life amidst deep social problems. Through symbols of time and various allusions, this short story highlights social inequality, the impact of war, and increasingly severe environmental exploitation. This research uses a qualitative descriptive approach with literary mimetic theory, to reveal how Danarto conveys social criticism in a subtle but sharp manner through characters trapped in difficult situations. The research results show that this short story invites readers to be more critical of existing social and cultural conditions, as well as providing reflections on the impact of social problems on human life. It is hoped that this research can contribute to the understanding of Indonesian literature and provide an appreciation for literary works that raise social issues.